Advanced Real-time Indoor Parking Localization based on Semi-Static Objects - Groh, Benjamin; Friedl, Martin; Linarth, Andre Guilherme; Angelopoulou, Elli (Proceeding of 17th International Conference on Information Fusion, 2014)
Indoor parking localization systems face two major challenges: the absence of GPS coverage and the dynamic character of the parking environment. The absence of GPS coverage can be compensated by data fusion of several sensors in order to localize an object in a map of the environment. However, this map may constantly change due to the dynamic nature of a parking garage. This paper describes an improvement to indoor localizations by a new map representation approach. The algorithm is developed for the application of an indoor parking system. The car park's map is based on the known permanent elements of the environment in combination with the knowledge of possibly changing elements. The permanent elements (e.g. walls) are considered static objects, while the known changing elements (e.g. parked cars) are modeled as semi-static objects. Such a representation avoids constantly updating the map with newly detected objects. Our algorithm fulfills the real-time requirement of the localization task for a computer-controlled car through the use of a particle filter. The filter uses laser scanner measurements and odometry data to localize the car in a precalculated probability grid map, containing static and semi-static elements. The evaluation of the algorithm in a real car park scenario demonstrates the robustness and real-time capability of the proposed system with a RMS error in the absolute position of 0.33m and in the heading angle of 1.03° at a computation time of 10ms per cycle.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.advanc

Efficient Implementation of the Singular Value Decomposition on a Reconfigurable System - Bobda, Christophe; Linarth, Andre Guilherme; et al. (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL2003), 2003)
We present a new implementation of the singular value decomposition (SVD) on a reconfigurable system made upon a Pentium processor and a FPGA-board plugged on a PCI slot of the PC. A maximum performance of the SVO is obtained by an efficient distribution of the data and the computation across the FPGA resource. Using the reconfiguration capability of the FPGA help us implement many operators on the same device. © Springer-Verlag Berlin Heidelberg 2003.
UnivIS-Import:2015-04-16:Pub.2003.tech.IMMD.inform.effici

Increasing the Flexibility in FPGA-Based Reconfigurable Platforms: The Erlangen Slot Machine - Ahmadinia, Ali; Bobda, Christophe; Haller, Thomas; Linarth, Andre Guilherme; Majer, Mateusz; Teich, Jürgen (IEEE 2005 Conference on Field-Programmable Technology, 2005)
We present a new concept as well as the implementation of an FPGA-based reconfigurable platform, the Erlangen Slot Machine (ESM). One main advantage of this platform is the possibility for each module to access its periphery independent from its location through a programmable crossbar, allowing an unrestricted relocation of modules on the device. Furthermore, we propose different intermodule communication structures. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IMMD.inform.increa

Robust lumen segmentation of coronary arteries in 2D angiographic images - Polyanskaya, Maria; Schwemmer, Chris; Linarth, Andre Guilherme; Lauritsch, Günter; Hornegger, Joachim (Medical Imaging 2012: Image Processing, 2012)
Diagnosis and treatment of coronary diseases depends on the data acquired during angiographic investigations. To provide better assistance for angiographic procedures, a segmentation of the lumen is required. A new algorithm for vessel centerline computation and lumen segmentation in 2D projection coronary angiograms is presented. Centerlines are extracted by a graph-based optimization technique, which searches for paths with minimal costs. The search starts from a source point, which is automatically set by the proposed algorithm. A new objective function for determining the costs of the graph edges is proposed. It consists of the response from the medialness filter and is regularized by the centerline potential function. In the medialness filter a vessel cross-section is represented by a 1D profile parameterized by center position and radius. The medialness filter at a point optimizes a gradient-based response over the profile radius. The proposed centerline potential function defines likeliness of each point of the image to be a centerline. Both the medialness filter and the centerline potential function are multi-scale. The entire lumen segmentation is achieved by the radii extracted during the medialness response computation. Application to clinical data shows that the presented algorithm segments coronary lumen with good accuracy and allows for subsequent assessment of the quantitative characteristics (i.e. diameter, curvature, etc.) of the vessels. © 2012 SPIE.

The Erlangen Slot Machine: A Highly Flexible FPGA-Based Reconfigurable Platform - Ahmadinia, Ali; Bobda, Christophe; Fekete, Sandor P.; Haller, Thomas; Linarth, Andre Guilherme; Majer, Mateusz; Teich, Jürgen; Van Der Veen, Jan C. (Proceedings of the 13th Annual IEEE Symposium on Field-Programmable Custom Computing Machines (FCCM'05), 2005)
We present a new concept as well as the implementation of an FPGA-based reconfigurable platform, the Erlangen Slot Machine (ESM). The main advantages of this platform are: first, the possibility for each module to access its peripheries independent from its location through a programmable crossbar, and distributed SRAMs among slices. This allows an unrestricted relocation of modules on the device. Second, the intermodule structure allows an unlimited communication among running modules. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IMMD.inform.theerl